Cover Picture: Development of ReaxFFSFOH Force Field for SF6‐H2O/O2 Hybrid System Based on Synergetic Optimization by CMA‐ES and MC Methodology (19/2021). Issue 19 (17th May 2021) - Liu, Heng; Wang, Jingrui; Li, Qingmin; Haddad, A. Manu
Abstract : The cover picture shows a gas insulated transmission line (GIL) undergoing partial discharge failure. Under such conditions, chemical reactions will occur between surface epoxy resin molecules, gas insulating medium (sulfur hexafluoride, SF6 ) and gas impurities (H2 O, O2, etc.), resulting in insulation deterioration. The ReaxFFSFOH force field lays a foundation for the study of the microscopic reaction mechanism of the SF6 ‐H2 O/O2 ‐epoxy system, which presents guiding significance for improving operational reliability of the GIL. More information can be found in the Full Paper by H. Liu et al. (DOI: 10.1002/slct.202101174 ).